Simultaneous determination of epinephrine and folic acid using MIL-101 (Fe)-NH2 metal-organic framework/graphene oxide nanocomposite modified electrode - Rasha Kareem Khudhur (ADMET and DMPK)
Background and purpose: It is generally known that the majority of disorders exhibit symptoms to some degree when the quantities of two crucial substances, epinephrine and folic acid, are low or high. These two chemicals' composition variations may be tracked and utilized to identify conditions such as myocardial infarction, Parkinson's disease, and mental disorders. Experimental approach: Using a solvothermal technique, we propose the synthesis of a novel MIL-101 (Fe)-NH2 metal-organic framework/graphene oxide nanocomposite (MOF/GO nanocomposite). The produced nanocomposite's morphology was examined using field-emission scanning electron microscopy. A straightforward, quick, and sensitive electrochemical sensing platform for epinephrine detection was then created by drop-casting the produced MOF/GO nanocomposite onto the screen-printed electrode (SPE). Key results: Compared to unmodified SPE, cyclic voltammetry revealed that the MOF/GO/SPE considerably enhanced the epinephrine oxidation process, exhibiting a greater detection current at a lower over-potential. The synergistic combination of MOF and GO sheets may cause this discovery. With a low detection limit of 0.07 μM, the MOF/GO/SPE sensor's linear response for voltammetric measurements of epinephrine was found to be between 0.2 and 500.0 μM. A modified electrode was also utilized to measure folic acid and epinephrine simultaneously. Conclusion: Lastly, the modified SPE effectively demonstrates its high accuracy in identifying folic acid and epinephrine in biological and pharmaceutical samples.